2000
DOI: 10.1080/21650993.2000.9755834
|View full text |Cite
|
Sign up to set email alerts
|

Singapore Social Work Students: Attitudes toward Older Adults

Abstract: and Balk well ( 1984) instrument, this study found that the attitudes of a sample of undergraduate Singaporean students ( n = 20 I) toward older adults were in the neutral range. A small minority (5.6%) was planning a career in gerontology. Comparisons of the findings were made with an American sample. Implications for social work education and future research were discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…22 A study of Singaporean undergraduate social work student attitudes reported that it was necessary to consider the impact of Confucian ethics on Singaporean students when assessing their attitudes towards older adults. 23 Moral codes and social norms are likely to be very much infl uenced by Confucianism in Singapore, where three quarters of the population are of Chinese descent. 24 The traditional basis for elder respect includes the Confucian teaching of fi lial piety 25 which prescribes for older persons to be respected and honoured by their offspring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 A study of Singaporean undergraduate social work student attitudes reported that it was necessary to consider the impact of Confucian ethics on Singaporean students when assessing their attitudes towards older adults. 23 Moral codes and social norms are likely to be very much infl uenced by Confucianism in Singapore, where three quarters of the population are of Chinese descent. 24 The traditional basis for elder respect includes the Confucian teaching of fi lial piety 25 which prescribes for older persons to be respected and honoured by their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…26 Even among Singaporeans of non-Chinese ancestry, such as the Malays, Indians, Pakistanis and Sri Lankans, where Confucianism is not practised, fi lial responsibility is also emphasised and practised. 23 Another possible reason is that many of the present elderly are active within their family arena, such as looking after their grandchildren, cooking and helping to keep the family traditions alive. 27 This could have the effect of letting the young witness fi rst-hand the active roles and functions older adults serve within the family.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a controlled study of undergraduate social work students in the USA, personal contact with older adults was significantly related to initial and substantial interest in ageing; the latter characterised by taking further gerontology courses and planning to work with older people [6]. Similarly, literature on student attitudes suggests that students are more positive toward older people where there has been a close personal relationship [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Australia, like other countries, has an ageing population (Borowski & Hugo 1997) and with the growth in associated services, the potential for social work practice with this population is considerable (Mehta et al . 2000; Scharlach et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, given that work with older people is often regarded as low status employment, it has not always been easy to recruit social workers in this area (Cummings et al . 2003), and, considering the complexity of issues facing this population, it is essential that those social workers who do work in the area are able to do so competently and reflectively (Mehta et al . 2000).…”
Section: Introductionmentioning
confidence: 99%